LEXICAL-STRUCTURAL FEATURES OF MYTHONYMS (Scientific journal of the Fergana State University, 2025)
Mythonyms are a term introduced to refer to words derived from or related to myths that play a role in the study of myths and narratives. This article analyzes the lexical and structural features of mythonyms, their origin, change and influence on modern language. Quantitative and qualitative analysis has been used to study the structure of mythonyms from classical and modern sources using a mixed method approach. Mythonyms share common features such as metaphor and symbolism, which often reflect the cultural context of their use. This article also highlights the structural variability of mythonyms, from related names to adjectives, and their role in enriching language. These concepts help to understand how myths affect language and perception, are a valuable resource for linguistics and literary studies.